2007
DOI: 10.1002/eji.200636838
|View full text |Cite
|
Sign up to set email alerts
|

MGL‐mediated internalization and antigen presentation by dendritic cells: A role for tyrosine‐5

Abstract: Professional antigen-presenting cells are essential for the initiation of adaptive immune responses; however, they also play a vital role in the maintenance of tolerance towards self-antigens. C-type lectins can function as antigen receptors by capturing carbohydrate ligands for processing and presentation. Here, we focused on the dendritic cell (DC)-expressed macrophage galactose-type lectin (MGL), a C-type lectin with a unique specificity for terminal GalNAc residues, such as the tumor-associated Tn antigen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…For some Ags the migratory DCs seem to act as simple ferries, while efficient CD8 ϩ T cell priming requires the transfer of Ag to LN-resident potentially MGL ϩ DCs (33,34). Furthermore, we demonstrated that MGL can also function as an genuine Ag uptake receptor that facilitates Ag presentation in MHC class II (35). Thus, the MGL-sinus interaction would certainly retain the immature DCs at their strategic localization.…”
Section: Discussionmentioning
confidence: 76%
“…For some Ags the migratory DCs seem to act as simple ferries, while efficient CD8 ϩ T cell priming requires the transfer of Ag to LN-resident potentially MGL ϩ DCs (33,34). Furthermore, we demonstrated that MGL can also function as an genuine Ag uptake receptor that facilitates Ag presentation in MHC class II (35). Thus, the MGL-sinus interaction would certainly retain the immature DCs at their strategic localization.…”
Section: Discussionmentioning
confidence: 76%
“…Alternatively, MGL1 itself could act as both an attachment and entry receptor for IAV. Therefore, we generated an MGL1 construct with 45 nucleotides (corresponding to 15 amino acids, including the putative internalization motif YENL [27,32,45]) deleted from its cytoplasmic domain (Fig. 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The MGL1 internalization assay was adapted from the protocol used by Van Vliet et al to examine internalization of MAb by human MGL (32). Briefly, cells were detached and incubated with 0.1 mg/ml biotin-labeled anti-mouse MGL MAb (clone ER-MP23; AbD Serotec) in TBS containing 10 mM CaCl 2 (TBS-Ca) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…MGL1 is highly specific for Lewis X and Lewis A structures, while MGL2, similar to the hMGL, recognizes N-GalNAc and galactose, including O-linked Tn-antigen, TFantigen, and core 2 structures [10]. hMGL is equipped with a partial dileucine zipper and with YENF internalization motifs [11]. This receptor is involved in the recognition of a large plethora of pathogens by DCs [12][13][14][15] and in the maintenance of T-cell homeostasis [16].…”
Section: Introductionmentioning
confidence: 99%